Nutrient-Driven O-GlcNAcylation at Promoters Impacts Genome-Wide RNA Pol II Distribution - Krause, Michael W.; Love, Dona C.; Ghosh, Salil K.; Wang, Peng; Yun, Sijung; Fukushige, Tetsunari; Hanover, John A. (Frontiers in Endocrinology, 2018)
Nutrient-driven O-GlcNAcylation has been linked to epigenetic regulation of gene expression in metazoans. In C. elegans, O-GlcNAc marks the promoters of over 800 developmental, metabolic, and stress-related genes; these O-GlcNAc marked genes show a strong 5’, promoter-proximal bias in the distribution of RNA Polymerase II (Pol II). In response to starvation or feeding, the steady state distribution of O-GlcNAc at promoters remain nearly constant presumably due to dynamic cycling mediated by the transferase OGT-1 and the O-GlcNAcase OGA-1. However, in viable mutants lacking either of these enzymes of O-GlcNAc metabolism, the nutrient-responsive GlcNAcylation of promoters is dramatically altered. Blocked O-GlcNAc cycling leads to a striking nutrient-dependent accumulation of O-GlcNAc on RNA Pol II. O-GlcNAc cycling mutants also show an exaggerated, nutrient-responsive redistribution of promoter-proximal RNA Pol II isoforms and extensive transcriptional deregulation. Our findings suggest a complex interplay between the O-GlcNAc modification at promoters, the kinase-dependent ‘CTD-code’, and co-factors regulating RNA Pol II dynamics. Nutrient-responsive O-GlcNAc cycling may buffer the transcriptional apparatus from dramatic swings in nutrient availability by modulating promoter activity to meet metabolic and developmental needs.